Changes in enzyme concentrations in mixed saliva during clinical manifestations of oral galvanosis - T. I. Ibragimov; L. B. Strogonova; G. F. Mamedova; V. V. Brovko; A. I. Ulyankin (Эндодонтия Today)
This article reviews the literature on the problem of the relationship between enzymes and changes in their concentrations in mixed saliva during clinical manifestations of galvanosis, as well as ways to determine their activity.